Contribution of Helicobacter pylori infection to the clinical and immunological profile of Common Variable Immunodeficiency - Raymundo, Adriana Motta (2022)
Tese de mestrado, Microbiologia Clínica e Doenças Infecciosas Emergentes, Universidade de Lisboa, Faculdade de Medicina, 2021